EVOLUTION OF INCLUSIVE EDUCATION POLICIES IN PORTUGAL (Education in the 21st Century, 2025)
Inclusive education in Portugal has undergone significant transformation over recent decades, driven by shifts in social, political, and legal frameworks that reflect a growing commitment to human rights and equal access to education. The movement from a historically segregated model to an integrated approach, catalysed by the Salamanca Declaration of 1994, has been pivotal in shaping contemporary educational practices. This study analyses how Portuguese policies on special needs education have evolved from the 1970s to the present and examines their implementation in practice in compulsory education. The primary objectives are to analyse the impact of key legislative changes, particularly Decree-Law 3/2008 and Decree-Law 54/2018, on the inclusivity of the education system and to assess how these policies have been operationalized in schools. The findings reveal that while significant progress has been made in integrating students with special needs into mainstream education, challenges remain in achieving uniform implementation and in ensuring that all educational professionals are adequately prepared to support diverse learning needs. The shift towards a more flexible and personalized educational approach, as mandated by recent legislation and inspired by the Salamanca principles, marks a crucial step towards a more inclusive education system.
Keywords: Special education; inclusive education; Portugal; Salamanca Declaration; Decree-Law 3/2008; Decree-Law 54/2018; paradigms; change; inclusion; equity